2016
DOI: 10.1016/j.cellsig.2015.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Arginine vasopressin receptor signaling and functional outcomes in heart failure

Abstract: Heart failure (HF) continues to be a highly prevalent syndrome, affecting millions of patients and costing billions of dollars in treatment per year in the United States alone. Studies in failing human heart and in transgenic HF models led to the recognition that enhanced neurohormonal signaling plays a causative role in HF progression, and the use of neurohormone receptor antagonists have proven to decrease hospitalization rates. It has also been long recognized that patients with HF have abnormal water reten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 165 publications
1
26
0
2
Order By: Relevance
“…However, a clear tendency towards increased plasma obestatin levels in chronic heart failure patients is observed, which becomes significant in those with cachexia, whilst elevated circulating concentrations of both obestatin and vasopressin are associated with cardiorenal syndrome (Xin et al ., ; Shi et al ., ). Indeed, obestatin is reported to inhibit experimental angiotensin II and dehydration‐induced release of vasopressin (Samson et al ., ), which is a key regulator of physiological fluid/electrolyte balance implicated in heart failure progression (Goldsmith and Gheorghiade, ; Wasilewski et al ., ). Although current data supporting direct cardiac effects of obestatin may be limited, such actions are likely to be significant given the established structural and functional changes that occur in diabetes and which are linked to markedly increased susceptibility to hypertension and ischaemia (Bugger and Abel, ).…”
Section: Cardiovascular Actions Of Obestatinmentioning
confidence: 97%
“…However, a clear tendency towards increased plasma obestatin levels in chronic heart failure patients is observed, which becomes significant in those with cachexia, whilst elevated circulating concentrations of both obestatin and vasopressin are associated with cardiorenal syndrome (Xin et al ., ; Shi et al ., ). Indeed, obestatin is reported to inhibit experimental angiotensin II and dehydration‐induced release of vasopressin (Samson et al ., ), which is a key regulator of physiological fluid/electrolyte balance implicated in heart failure progression (Goldsmith and Gheorghiade, ; Wasilewski et al ., ). Although current data supporting direct cardiac effects of obestatin may be limited, such actions are likely to be significant given the established structural and functional changes that occur in diabetes and which are linked to markedly increased susceptibility to hypertension and ischaemia (Bugger and Abel, ).…”
Section: Cardiovascular Actions Of Obestatinmentioning
confidence: 97%
“…Consistent with these studies, cardiomyocyte-restricted ( α MHC-tTA driven) V1AR transgenic (V1ARTg) mice, with five times the expression of endogenous V1AR, developed LV hypertrophy, dilatation, reduced contractile performance and fetal gene reprogramming with progressive aging [7]. In addition, we reported that cardiac V1AR expression is increased 2-fold in human HF [6], as well as in mouse [8] and dog [5] models of HF, and that chronic V1AR inhibition during transaortic constriction (TAC) restored V1AR expression and cardiac function in mice [8]. …”
Section: Discussionmentioning
confidence: 76%
“…Several agonists including norepinephrine, angiotensin II and vasopressin (VP) acting on Gq-protein coupled receptors induce hypertrophy of cardiac myocytes [ [1] , [2] , [3] , [4] , [5] ]. Gq-protein coupled receptors activate phospholipase C (PLC) resulting in the generation of the soluble second messenger, inositol (1,4,5) trisphosphate (IP 3 ) and the membrane-bound diacylglycerol (DG).…”
Section: Introductionmentioning
confidence: 99%